2017
DOI: 10.3389/fpsyg.2017.02065
|View full text |Cite
|
Sign up to set email alerts
|

Age Bias in Selection Decisions: The Role of Facial Appearance and Fitness Impressions

Abstract: This research examined the impact of facial age appearance on hiring, and impressions of fitness as the underlying mechanism. In two experimental hiring simulations, one with lay persons and one with Human Resource professionals, participants evaluated a chronologically older or younger candidate (as indicated by date of birth and age label) with either younger or older facial age appearance (as indicated by a photograph). In both studies, older-looking candidates received lower hireability ratings, due to les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
(67 reference statements)
2
20
0
Order By: Relevance
“…However, our research revealed that appearance is especially important when no information or only a little other information is available (Olivola et al, 2012). In line with previous research, we would expect the impact of facial appearance on leader selection to decrease when information about competence is available because competence-related information should have a greater impact on selection decisions (Kaufmann et al, 2017). Although facial appearance had an impact on women’s chances of getting more nominations in the leadership contest in this study, we would expect this effect to diminish in the medium and long terms after women have entered the work place.…”
Section: Discussionsupporting
confidence: 77%
“…However, our research revealed that appearance is especially important when no information or only a little other information is available (Olivola et al, 2012). In line with previous research, we would expect the impact of facial appearance on leader selection to decrease when information about competence is available because competence-related information should have a greater impact on selection decisions (Kaufmann et al, 2017). Although facial appearance had an impact on women’s chances of getting more nominations in the leadership contest in this study, we would expect this effect to diminish in the medium and long terms after women have entered the work place.…”
Section: Discussionsupporting
confidence: 77%
“…We want to point out that the profiles only included positive traits and that it is often argued that emphasizing positive traits may be effective in counteracting ageism (e.g., Kaufmann et al., 2017; Levy, 1996, 2017). However, in our study positive old traits resulted in discriminatory behavior when compared to neutral or young traits.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have found that age prejudice has a negative impact on older adults in a variety of domains, including in the medical care they receive, their experiences in the workplace, and their mental functioning (e.g., Avolio & Barrett, 1987;Barakat et al, 1999;Barber & Mather, 2013;Kagan & Melendez-Torres, 2015;Kaufmann et al, 2017;Rupp et al, 2006). Furthermore, those who hold biases against older adults are also affected negatively by their own biases-primarily as it relates to health and well-being (Levy et al, 2009(Levy et al, , 2016Levy & Myers, 2004;Levy, Zonderman, et al, 2012).…”
Section: Bias Against Older Adultsmentioning
confidence: 99%